Zirconium-aluminum composite powder preparation and synthesis process and zirconium-aluminum composite powder

By using a spiral microchannel reactor for mixing and dispersion during the zirconium aluminum powder composite process, the problems of uneven dispersion and long mixing time are solved, and uniform bonding and efficient production of zirconium aluminum composite powder are achieved.

CN119462092APending Publication Date: 2025-02-18XIANGTAN SHUNLUO ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411666759.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the existing zirconium aluminum powder composite process, there are problems such as uneven dispersion of powder, long mixing time and low efficiency.

Method used

The spiral microchannel reactor is used to mix and disperse zirconium liquid, alumina and alkaline precipitant. By adjusting the feed ratio and temperature, uniform dispersion of zirconium-aluminum composite powder is achieved, and uniformity is obtained through calcination, crushing and granulation steps. Dispersed zirconium-aluminum composite powder.

Benefits of technology

The uniform combination of zirconium-aluminum composite powder is achieved, the mixing time is shortened, the production efficiency is improved, energy consumption and production costs are reduced, and there is no wastewater discharge, achieving green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462092A_ABST
    Figure CN119462092A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation and synthesis process of zirconium-aluminum composite powder and the zirconium-aluminum composite powder, which are used for solving the technical problems of non-uniform powder dispersion, long mixing time and low efficiency in the existing zirconium-aluminum powder compounding process. The preparation and synthesis process of the zirconium-aluminum composite powder comprises the following steps: S1, respectively and simultaneously feeding zirconium liquid, aluminum oxide and an alkaline precipitant which are prepared in advance into a spiral micro-channel reactor for mixing and dispersing, and adjusting the feeding ratio according to the composite ratio of the required zirconium-aluminum composite powder, the temperature of the spiral micro-channel reactor is maintained at 10-40 DEG C, and zirconium-aluminum composite powder slurry is obtained; and S2, calcining, crushing and granulating the zirconium-aluminum composite powder slurry to obtain the uniformly dispersed zirconium-aluminum composite powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zirconium-aluminum composite powder preparation, and in particular to a zirconium-aluminum composite powder preparation synthesis process and zirconium-aluminum composite powder. Background Art

[0002] Alumina ceramics are the most widely used ceramic materials at present. They have excellent chemical stability, mechanical properties and electrical properties. However, they are brittle and have poor fracture toughness, so their application range is limited. Zirconia has the advantages of high melting point, high hardness, acid and alkali corrosion resistance, and strong toughness, but it has the property of low-temperature aging, and microcracks or even breakage will occur in the structure, so its application range is also limited. The composite of alumina and zirconia is an effective way to solve this problem.

[0003] In recent years, new composite methods of alumina and zirconia have emerged, including mechanical mixing method, buffer solution method (co-precipitation), solution-gel method, precipitation coating method, rapid solidification method, etc.

[0004] At present, the most commonly used method in China is mechanical mixing. This method generally uses finished Al2O3 powder and ZrO2 powder to make mixed powder after ball milling. Ball milling has the functions of mixing and dispersing and refining powder particles. However, this method has many problems:

[0005] (1) Fine powder is easily produced during the ball milling process. The connection between alumina and zirconia is weak, and zirconia and alumina cannot be effectively combined. The powders combine with themselves to form agglomerates that cannot be opened.

[0006] (2) The ball milling process consumes a lot of energy and the powders are difficult to mix evenly. If a ball mill plus solvent is used for mixing, it takes a long time (24h to 40h) of ball milling and then filtering and sintering. This method can achieve a more uniform mixing and improve the bonding of zirconia and alumina powders. However, the ball milling time is long, and the wear and friction between the grinding media and the heating of the materials will result in energy loss, long processing time, and high production costs.

[0007] Therefore, finding a technical solution that can solve the above technical problems has become an important topic studied by technical personnel in this field. Summary of the invention

[0008] The embodiment of the invention discloses a zirconium-aluminum composite powder preparation and synthesis process and zirconium-aluminum composite powder, which are used to solve the technical problems of uneven powder dispersion, long mixing time and low efficiency in the existing zirconium-aluminum powder composite process.

[0009] The present invention provides a process for preparing and synthesizing zirconium-aluminum composite powder, comprising the following steps:

[0010] S1. The pre-prepared zirconium liquid, alumina and alkaline precipitant are respectively introduced into a spiral microchannel reactor for mixing and dispersion, and the feed ratio is adjusted according to the composite ratio of the desired zirconium-aluminum composite powder, and the temperature of the spiral microchannel reactor is maintained at 10-40° C. to obtain a zirconium-aluminum composite powder slurry;

[0011] S2. After calcining, crushing and granulating the zirconium-aluminum composite powder slurry, uniformly dispersed zirconium-aluminum composite powder can be obtained.

[0012] Optionally, in step S1, the mixed material in the microchannel reactor flows at a flow rate of not less than 2.5 m / s.

[0013] Optionally, the zirconium liquid is a zirconium oxychloride solution, and its concentration is between 8% and 30%.

[0014] Optionally, the alumina is selected from α-alumina, and its fluidity is between 50-80s.

[0015] Optionally, the alkaline precipitant is ammonia water, and the concentration of the ammonia water is between 8% and 25%.

[0016] Optionally, in step S2, the feed ratio of the zirconium liquid, the alumina and the alkaline precipitant is:

[0017] Zirconium liquid: alumina: alkalinity = 1: 0.01-50: 4-50.

[0018] Optionally, in step S1, the alkaline precipitant is added in an amount such that the pH of the zirconium-aluminum composite powder slurry flowing out from the outlet of the spiral microchannel reactor is between 8.5 and 12.

[0019] Optionally, in step S1, the residence time of the zirconium-aluminum composite powder slurry in the spiral microchannel reactor is not more than 20 minutes.

[0020] Optionally, the diameter of the feed port of the spiral microchannel reactor is 1 cm, the total length of the material flow is 50 m, and the total volume is 40 L.

[0021] The present invention provides a zirconium-aluminum composite powder, which is prepared by the above-mentioned zirconium-aluminum composite powder preparation and synthesis process.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The process of this embodiment applies a spiral microchannel reactor to powder mixing, and applies the axial back mixing phenomenon of materials in the spiral microchannel to the mixing of materials. Compared with the traditional mechanical mixing method, zirconium oxide and aluminum oxide can be evenly combined under this process, and the whole mixing process is stable, thereby improving the purity and yield of the final zirconium-aluminum composite powder, and effectively shortening the mixing time, improving production efficiency, and no wastewater is discharged in the whole process, thereby realizing green production, saving energy consumption, and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 A schematic diagram of a process for preparing and synthesizing a zirconium-aluminum composite powder provided by the present invention;

[0026] Figure 2 A schematic diagram of the structure of a spiral microchannel reactor involved in a process for preparing and synthesizing zirconium-aluminum composite powder provided by the present invention;

[0027] Figure 3 This is a 5um scale SEM image of the ceramic sheet prepared in Example 1 of the present invention;

[0028] Figure 4 This is a 10um scale SEM image of the ceramic sheet prepared in Example 1 of the present invention;

[0029] Figure 5 This is a 50um scale SEM image of the ceramic sheet prepared in Example 2 of the present invention;

[0030] Illustrations: 1- zirconium liquid storage tank; 2- alumina storage tank; 3- alkaline precipitant storage tank; 4- metering pump; 5- spiral microchannel reactor; 6- push plate furnace. DETAILED DESCRIPTION

[0031] The invention discloses a zirconium-aluminum composite powder preparation and synthesis process and zirconium-aluminum composite powder, which are used to solve the technical problems of uneven powder dispersion, long mixing time and low efficiency in the existing zirconium-aluminum powder composite process.

[0032] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] See also Figure 1 to Figure 2 The present invention provides a zirconium-aluminum composite powder preparation and synthesis process, comprising the following steps:

[0034] S1. The pre-prepared zirconium liquid, alumina and alkaline precipitant are respectively introduced into a spiral microchannel reactor for mixing and dispersion, and the feed ratio is adjusted according to the composite ratio of the desired zirconium-aluminum composite powder, and the temperature of the spiral microchannel reactor is maintained at 10-40° C. to obtain a zirconium-aluminum composite powder slurry;

[0035] In the above step S1, a sufficient amount of alkaline precipitant reacts with the zirconium liquid to generate zirconium hydroxide colloidal particles, and the zirconium hydroxide colloidal particles are evenly coated around the aluminum oxide during the flow process;

[0036] S2. After calcining, crushing and granulating the zirconium-aluminum composite powder slurry, uniformly dispersed zirconium-aluminum composite powder can be obtained.

[0037] The process of the present invention applies a spiral microchannel reactor to powder mixing, and applies the axial back-mixing phenomenon of materials in the spiral microchannel to the mixing of materials. Compared with the traditional mechanical mixing method, zirconium oxide and aluminum oxide can be evenly combined under this process, and the whole mixing process is stable, thereby improving the purity and yield of the final zirconium-aluminum composite powder, and effectively shortening the mixing time, improving production efficiency, and no wastewater is discharged in the whole process, thereby realizing green production, saving energy consumption, and reducing production costs.

[0038] Furthermore, in step S1 of the present invention, the mixed material in the microchannel reactor flows at a flow rate of not less than 2.5 m / s.

[0039] It should be noted that by setting the flow rate of the above-mentioned mixed materials, the mixed materials can be fully reacted and mixed in the spiral microchannel reactor. If the flow rate is too low, the fluidity between the materials is poor and the reaction mixing cannot be effectively achieved.

[0040] Furthermore, the zirconium liquid used in the present invention is specifically a zirconium oxychloride solution, and its concentration is between 8% and 30%.

[0041] It should be noted that, in some specific embodiments, the above concentration may be 9%, 10%, 15%, etc. The present invention is not limited to this.

[0042] Furthermore, the alumina used in the present invention is selected from α-alumina, and its fluidity is between 50-80s.

[0043] It should be noted that in some specific embodiments, the above fluidity may be 60S, 70S, 75S, etc. The present invention is not limited to this.

[0044] Furthermore, the alkaline precipitant used in the present invention is aqueous ammonia.

[0045] It should be noted that the concentration of the ammonia water is between 8% and 25%.

[0046] Furthermore, in step S2 of the present invention, the feed ratio of the zirconium liquid, the alumina and the alkaline precipitant is:

[0047] Zirconium liquid: alumina: alkalinity = 1: 0.01-50: 4-50.

[0048] It should be noted that the above ratio is adjusted according to the required composite ratio of the zirconium-aluminum composite powder. In some specific embodiments, the above ratio can be 1:0.02:5 or 1:30:40, etc., and the present invention is not limited to this.

[0049] Furthermore, in step S1 of the present invention, the alkaline precipitant is added in such an amount that the pH of the zirconium-aluminum composite powder slurry flowing out from the outlet of the spiral microchannel reactor is between 8.5 and 12.

[0050] It should be noted that, in some specific embodiments, the pH may be 9, 10, 11, etc. The present invention is not limited thereto.

[0051] Furthermore, in step S1 of the present invention, the residence time of the zirconium-aluminum composite powder slurry in the spiral microchannel reactor is not more than 20 minutes.

[0052] It should be noted that, in some specific embodiments, the above-mentioned residence time can be 10 minutes, 15 minutes, 18 minutes, etc.

[0053] Furthermore, the diameter of the feed port of the spiral microchannel reactor used in the present invention is 1 cm, the total length of the material flow is 50 m, and the total volume is 40 L.

[0054] Specifically, the external dimensions of the spiral microchannel reactor in the present invention are: 0.5 m in length and 0.5 m in width.

[0055] In addition, in the spiral microchannel reactor used in the present invention, the fluid has a back-mixing phenomenon in the axial flow from a microscopic point of view.

[0056] See also Figure 1 to Figure 2 The present invention provides a zirconium-aluminum composite powder, which is prepared by the above-mentioned zirconium-aluminum composite powder preparation and synthesis process.

[0057] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0058] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0059] Example 1

[0060] A zirconium oxychloride solution with a concentration of 20%, alumina with a flow rate of 68s and ammonia water with a concentration of 25% were selected, and the materials were put into the corresponding material tanks in the ratio of zirconium oxychloride: alumina: ammonia water = 1:2:8. At the same time, the metering pump was started to feed the material into the spiral microchannel reactor. The total feed flow rate was 40ml / s, and the residence time of the material in the microchannel was 15min.

[0061] After flowing through the microchannel reactor, the material flows out from the outlet and enters the push plate furnace for calcination. After crushing, a zirconia-alumina composite powder with uniform composition and firm combination is obtained.

[0062] The synthesized powder was crushed and added with a binder before dry pressing. After cold isostatic pressing, the binder was removed and sintered at a sintering temperature of 1560°C for 4 hours to obtain the corresponding ceramic sheet. The surface of the obtained ceramic sheet was observed microscopically. The results are as follows Figure 3 to Figure 4 As shown, the ceramic sheet obtained was tested and the density of the ceramic material was measured to be 4.15 g / cm 3 .

[0063] Example 2

[0064] A zirconium oxychloride solution with a concentration of 20%, alumina with a flow rate of 68s and ammonia water with a concentration of 25% were selected, and the materials were put into the corresponding material tanks in the ratio of zirconium oxychloride: alumina: ammonia water = 20:1:14. At the same time, the metering pump was started to feed the material into the microchannel reactor. The total feed flow rate was 33ml / s, and the residence time of the material in the microchannel was 20min.

[0065] After flowing through the microchannel reactor, the material flows out from the outlet and enters the push plate furnace for calcination. After crushing, a zirconia-alumina composite powder with uniform composition and firm combination is obtained.

[0066] The synthesized powder was crushed and added with a binder before dry pressing. After cold isostatic pressing, the binder was removed and sintered at a sintering temperature of 1530°C for 4 hours to obtain the corresponding ceramic sheet. The surface of the obtained ceramic sheet was observed microscopically. The results are as follows Figure 5 As shown, the obtained ceramic sheet was tested and the density of the ceramic material was measured to be 5.86 g / cm 3 .

[0067] Comparative Example 1

[0068] According to the ratio in Example 1, the above raw materials were selected, and the alumina powder and zirconium oxide powder were dispersed in the ball mill for 12 hours respectively, and then ball milled for 6 hours. The mixed slurry was filter-filtered and sintered at a sintering temperature of 1060°C for 4 hours to obtain zirconium oxide toughened alumina powder. The synthesized powder was prepared into ceramic sheets according to the ceramic making steps in Example 1 for testing, and its density was measured to be 4.10g / cm 3 .

[0069] Comparative Example 2

[0070] According to the ratio in Example 2, the above raw materials were selected, and the alumina powder and zirconium oxide powder were dispersed in the ball mill for 12 hours, and then ball milled for 6 hours. The mixed slurry was filter-filtered and sintered at a sintering temperature of 1060°C for 4 hours to obtain zirconium oxide toughened alumina powder. The synthesized powder was prepared into ceramic sheets according to the ceramic making steps in Example 2 for testing, and its density was measured to be 5.80g / cm 3 .

[0071] The above is a detailed introduction to the preparation and synthesis process of a zirconium-aluminum composite powder and the zirconium-aluminum composite powder provided by the present invention. For a person skilled in the art, according to the ideas of the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A process for preparing and synthesizing zirconium-aluminum composite powder, characterized in that: The following steps are involved: S1. The pre-prepared zirconium liquid, alumina and alkaline precipitant are respectively introduced into a spiral microchannel reactor for mixing and dispersion, and the feed ratio is adjusted according to the composite ratio of the desired zirconium-aluminum composite powder, and the temperature of the spiral microchannel reactor is maintained at 10-40° C. to obtain a zirconium-aluminum composite powder slurry; S2. After calcining, crushing and granulating the zirconium-aluminum composite powder slurry, uniformly dispersed zirconium-aluminum composite powder can be obtained.

2. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: In the step S1, the mixed material in the microchannel reactor flows at a flow rate of not less than 2.5 m / s.

3. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: The zirconium liquid is a zirconium oxychloride solution, and its concentration is between 8% and 30%.

4. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: The alumina is selected from α-alumina, and its fluidity is between 50-80s.

5. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: The alkaline precipitant is ammonia water, and the concentration of the ammonia water is between 8% and 25%.

6. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: In the step S2, the feed ratio of the zirconium liquid, the alumina and the alkaline precipitant is: zirconium liquid: alumina: alkaline = 1: 0.01-50: 4-50.

7. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: In the step S1, the alkaline precipitant is added in an amount such that the pH of the zirconium-aluminum composite powder slurry flowing out from the outlet of the spiral microchannel reactor is between 8.5 and 12.

8. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: In the step S1, the residence time of the zirconium-aluminum composite powder slurry in the spiral microchannel reactor is not more than 20 minutes.

9. The process for preparing and synthesizing zirconium-aluminum composite powder according to claim 1, characterized in that: The diameter of the feed port of the spiral microchannel reactor is 1 cm, the total length of the material flow is 50 m, and the total volume is 40 L.

10. A zirconium-aluminum composite powder, characterized in that: The zirconium-aluminum composite powder is obtained by the zirconium-aluminum composite powder preparation and synthesis process described in any one of claims 1 to 9.